AGA129 collaborative teaching event highlights real-world Chemistry applications - Johar, Nurain; Mansur, Nurul Syahirah; Mohamed Idris, Hazfina; Mohamed, Bebe Norlita; Poli, Firus Musfirah (Corporate Communication Unit, UiTM Mukah Campus, 2025)
The three-hour session began with a syllabus-based lecture on the Introduction to Reactions of Organic Compounds, providing students with foundational knowledge aligned with their coursework. Following this, ChM. Siti Hajar, who has served as a professional chemist since 2013, conducted an insightful sharing session covering toxicology in herbal products, the importance of organic chemistry in toxicological analysis, and her hands-on experience with analytical instruments such as Gas Chromatography Mass Spectrometry (GC-MS) and Gas Chromatography-Flame Ionization Detector (GC-FID).